Mechanism by which ferric iron promotes the bioleaching of arsenopyrite by the moderate thermophile Sulfobacillus thermosulfidooxidans. (June 2019) - Zhang, Duo-Rui; Xia, Jin-Lan; Nie, Zhen-Yuan; Chen, Hong-Rui; Liu, Hong-Chang; Deng, Yu; Zhao, Yi-Dong; Zhang, Li-Li; Wen, Wen; Yang, Hong-Ying
Graphical abstract: Highlights: Promotion mechanism of additive Fe 3+ on arsenopyrite bioleaching was studied. Fe, As and S speciation during arsenopyrite bioleaching was evaluated. Ammoniojarosite plays the key role in forming the loose and porous surface structure. The additive Fe 3+ significantly promote the cell's apparent Fe/S oxidation activities. Fe 3+ and S . thermosulfidooxidans synergistically promote S 0 and As2 S3 elimination. Abstract: In this study, the mechanisms by which ferric iron promotes bioleaching of arsenopyrite by the moderately thermoacidophilic strain Sulfobacillus thermosulfidooxidans YN-22 was evaluated for the first time by integrating Fe L-edge and As/S K-edge X-ray absorption near edge structure (XANES) spectroscopy with Fourier transform infrared spectroscopy (FT-IR), synchrotron radiation X-ray diffraction (SR-XRD), Raman spectroscopy, and scanning electron microscopy (SEM), and the leaching parameters were also determined. The results showed that the addition of Fe 3+ (6 g/L) significantly promoted bioleaching of arsenopyrite by enhancing the cell growth and the (bio)degradation of elemental sulfur (S 0 ) and orpiment (As2 S3 ) intermediates on the mineral surface. In addition, an increased formation of loose particulate structures containing the Fe(III)-containing products jarosite (mainly ammoniojarosite), scorodite (ferric arsenate) and schwertmannite was observed.